2016
DOI: 10.1007/s00213-016-4432-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of regulator of G protein signaling 4 in delta-opioid receptor-mediated behaviors

Abstract: Rationale Regulator of G protein signaling (RGS) proteins act as negative modulators of G protein signaling. RGS4 has been shown to negatively modulate G protein signaling mediated by the delta opioid receptor (DOPr) in vitro. However, the role of RGS4 in modulating DOPr-mediated behaviors in vivo has not been elucidated. Objective The aim of this study was to compare the ability of the DOPr agonist SNC80 to induce DOPr-mediated antinociception, antihyperalgesia, antidepressant-like effects, and convulsions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 35 publications
(47 reference statements)
8
33
0
Order By: Relevance
“…The potency of SNC80 to produce antihyperalgesia and antidepressant‐like effects was significantly increased in the Gα o RGS‐insensitive heterozygous mice. These data indicate that these δ‐receptor‐mediated behaviours signal through Gα o and are negatively regulated by RGS proteins, consistent with our previous finding that RGS4 negatively regulates these behaviours (Dripps et al, ). Furthermore, these enhanced effects of SNC80 were observed in mice with only one mutant copy of Gα o , demonstrating that δ‐receptor‐mediated signalling in vivo is highly sensitive to the effects of RGS proteins.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The potency of SNC80 to produce antihyperalgesia and antidepressant‐like effects was significantly increased in the Gα o RGS‐insensitive heterozygous mice. These data indicate that these δ‐receptor‐mediated behaviours signal through Gα o and are negatively regulated by RGS proteins, consistent with our previous finding that RGS4 negatively regulates these behaviours (Dripps et al, ). Furthermore, these enhanced effects of SNC80 were observed in mice with only one mutant copy of Gα o , demonstrating that δ‐receptor‐mediated signalling in vivo is highly sensitive to the effects of RGS proteins.…”
Section: Discussionsupporting
confidence: 92%
“…We found that Gα o and arrestins differentially regulate the antihyperalgesia, antidepressant‐like effects and convulsions produced by the δ‐receptor agonist SNC80. In the NTG‐induced thermal hyperalgesia assay, SNC80 produced antihyperalgesia in wild‐type mice, consistent with previous studies (Pradhan et al, ; Dripps et al, ). SNC80 also decreased immobility in the FST, consistent with the well‐established antidepressant‐like effects of δ‐receptor agonists (Broom et al, ; Naidu et al, ; Saitoh et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, when similar experiments were performed using the truncated DΝ 17 RGS4 preincubated with increasing concentrations of i4 peptide, no shift in protein migration was observed, suggesting that the DΝ 17 RGS4 charge and its hydrodynamic size remained unchanged (Fig. 4B, lanes [14][15][16]. Similarly, no alterations in protein charge were detected using the control peptide MELVPSAR (Fig.…”
Section: Helix 8 Of D-or Determines Rgs4 Interactionmentioning
confidence: 81%